Late-sown lentil performance in response to foliar application of zinc (Bangladesh Journal of Botany, 2015)
Highest and lowest plant height at harvest was recorded with application of 0.08% Zn and in control treatment, respectively. Longest and shortest roots were recorded in the plots treated with 0.08% Zn and control respectively. Zn treatment of 0.04% produced maximum lentil seed whereas lowest was recorded under control. DOI: http://dx.doi.org/10.3329/bjb.v44i1.22734 Bangladesh J. Bot. 44(1): 125-128, 2015 (March)